Genomic Analysis of Caldithrix abyssi, the Thermophilic Anaerobic Bacterium of the Novel Bacterial Phylum Calditrichaeota - Kublanov, Ilya V.; Sigalova, Olga M.; Gavrilov, Sergey N.; Lebedinsky, Alexander V.; Rinke, Christian; Kovaleva, Olga; Chernyh, Nikolai A.; Ivanova, Natalia; Daum, Chris; Reddy, T.B.K.; Klenk, Hans-Peter; Spring, Stefan; et al. (Frontiers in Microbiology, 2017)
The genome of Caldithrix abyssi, the first cultivated representative of a phylum-level bacterial lineage, was sequenced within the framework of Genomic Encyclopedia of Bacteria and Archaea (GEBA) project. The genomic analysis revealed mechanisms allowing this anaerobic bacterium to ferment peptides or to implement nitrate reduction with acetate or molecular hydrogen as electron donors. The genome encoded five different [NiFe]- and [FeFe]-hydrogenases, one of which, group 1 [NiFe]-hydrogenase, is presumably involved in lithoheterotrophic growth, three other produce H2 during fermentation, and one is apparently bidirectional. The ability to reduce nitrate is determined by a nitrate reductase of the Nap family, while nitrite reduction to ammonia is presumably catalyzed by an octaheme cytochrome c nitrite reductase εHao. The genome contained genes of respiratory polysulfide/thiosulfate reductase, however, elemental sulfur and thiosulfate were not used as the electron acceptors for anaerobic respiration with acetate or H2, probably due to the lack of the gene of the maturation protein. Nevertheless, elemental sulfur and thiosulfate stimulated growth on fermentable substrates (peptides), being reduced to sulfide, most probably through the action of the cytoplasmic sulfide dehydrogenase and/or NAD(P)-dependent [NiFe]-hydrogenase (sulfhydrogenase) encoded by the genome. Surprisingly, the genome of this anaerobic microorganism encoded all genes for cytochrome c oxidase, however its maturation machinery seems to be non-operational due to genomic rearrangements of supplementary genes. Despite the fact that sugars were not among the substrates reported when C. abyssi was first described, our genomic analysis revealed multiple genes of glycoside hydrolases, and some of them were predicted to be secreted. This finding aided in bringing out four carbohydrates that supported the growth of C. abyssi: starch, cellobiose, glucomannan and xyloglucan. The genomic analysis demonstrated the ability of C. abyssi to synthesize nucleotides and most amino acids and vitamins. Finally, the genomic sequence allowed us to perform a phylogenomic analysis, based on 38 protein sequences, which confirmed the deep branching of this lineage and justified the proposal of a novel phylum Calditrichaeota.